Spanish Basic Course Units 1-15 - Stockwell, Robert P.; Foreign Service (Department of State), Washington, DC. Foreign Service Inst. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1961)
This course, designed by the Foreign Service Institute in 1957, was prepared to train officers of the Foreign Service and of the United States government agencies who are involved in foreign affairs and who need to learn to speak Spanish. The course is designed to be taught by a native speaker of Spanish. Normally, the class is limited to six students who receive six hours of class drill daily and are expected to do two hours of preparatory study daily, primarily with the use of tapes. Following this method, each unit requires two and a half days to assimilate the materials thoroughly. The 15 units contain materials on: basic sentences, pronunciation drills, pattern drills, replacement drills, variation drills, conversation stimulus, irregular verbs, and tenses. A vocabulary section and grammar index are included. Many of the drills are presented in Spanish, in phonetic transcription, and in English. For the companion documents see FL 002 663, FL 002 664, and FL 002 665. (RL)
Availability: Superintendent of Documents, U.S. Government Printing Office, Washington, D.C. 20402 (GPO-0-373-662, $6.00).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Audiolingual Methods; Basic Skills; Conversational Language Courses; Cultural Education; Grammar; Instructional Materials; Intensive Language Courses; Language Instruction; Language Patterns; Pattern Drills (Language); Reading Development; Second Language Learning; Spanish; Vocabulary Development